If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -5x = 7 + 13x Solving 1 + -5x = 7 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 1 + -5x + -13x = 7 + 13x + -13x Combine like terms: -5x + -13x = -18x 1 + -18x = 7 + 13x + -13x Combine like terms: 13x + -13x = 0 1 + -18x = 7 + 0 1 + -18x = 7 Add '-1' to each side of the equation. 1 + -1 + -18x = 7 + -1 Combine like terms: 1 + -1 = 0 0 + -18x = 7 + -1 -18x = 7 + -1 Combine like terms: 7 + -1 = 6 -18x = 6 Divide each side by '-18'. x = -0.3333333333 Simplifying x = -0.3333333333
| p(x+q)=q | | 3x+x+50+90=180 | | 48=16x^2 | | 100+2x+6x=180 | | P(63000)=10(63000)-2000 | | 3x-12=1x-2 | | 5/14x=-1/2 | | 12+22kx=-46x | | 0=(x^2-2x) | | [z-8]+4=8 | | f(x)=4x^2-32x-3 | | 7y+27=15x-5 | | -3(x+3)+2=x+5 | | -9[72-1]-3=-57 | | 14=3*r/1.5 | | x/2=7/12 | | 3x+4xy=7 | | h(t)=-16t^2+128t+3 | | 1.1x+2.7=2.1x+3.7 | | .5(y-8)=2x | | (7x-4)+(3x+8)= | | 4y-7=-8x-3 | | 6+5m=51 | | 4d-d= | | 5+5x+y=100 | | 9y-16=65 | | 4(x-12)=8+12x | | -y+1=x+7 | | 5w+w+w= | | 19+6x=8x-5(x-4) | | 7(7m-8)= | | 8x-4=2-6 |